2021
DOI: 10.1519/jsc.0000000000003918
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Mass and Fat Mass Relationships With Physical Fitness Test Performance in Law Enforcement Recruits Before Academy

Abstract: The purpose of this study was to analyze relationships between skeletal muscle mass percentage (SMM%) and fat mass percentage (FM%) relative to fitness test performance in law enforcement recruits. Retrospective analysis was conducted on 338 recruits (271 males, 67 females) from four academy classes. SMM% and FM% were measured using cost-effective and practical bioelectrical impedance analysis (BIA) equipment that used hand and foot placement. The fitness tests included: grip strength; vertical jump; 75-yard p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Body mass and FM% were recorded by electronic digital scales (Model HBF-510, Omron Healthcare, Kyoto, Japan), which included bioelectrical impedance analysis. The equipment used in this study has been found to be reliable (intraclass correlation coefficient ≥0.95-0.99) in men and women [39,40], and has been previously used in law enforcement populations [41]. Manufacturer guidelines were followed to record FM% [39], and the procedures used were also reported by Lockie et al [41].…”
Section: Resting Heart Rate (Rhr) and Blood Pressure (Bp)mentioning
confidence: 76%
See 2 more Smart Citations
“…Body mass and FM% were recorded by electronic digital scales (Model HBF-510, Omron Healthcare, Kyoto, Japan), which included bioelectrical impedance analysis. The equipment used in this study has been found to be reliable (intraclass correlation coefficient ≥0.95-0.99) in men and women [39,40], and has been previously used in law enforcement populations [41]. Manufacturer guidelines were followed to record FM% [39], and the procedures used were also reported by Lockie et al [41].…”
Section: Resting Heart Rate (Rhr) and Blood Pressure (Bp)mentioning
confidence: 76%
“…The equipment used in this study has been found to be reliable (intraclass correlation coefficient ≥0.95-0.99) in men and women [39,40], and has been previously used in law enforcement populations [41]. Manufacturer guidelines were followed to record FM% [39], and the procedures used were also reported by Lockie et al [41]. The age, height in cm, and sex of the LEO were entered into the device, and the LEO wore no shoes or socks.…”
Section: Resting Heart Rate (Rhr) and Blood Pressure (Bp)mentioning
confidence: 88%
See 1 more Smart Citation
“…Body mass and BF% were recorded by a bioelectrical impedance analysis (BIA) device (Tanita Corporation, Tokyo, Japan). Previous police research has utilised BIA in body composition analyses [33]. Protocol guidelines provided by the manufacturer were used to record body mass via BIA [33,34].…”
Section: Height Body Mass and Body Fat Percentage (Bf%)mentioning
confidence: 99%
“…Previous police research has utilised BIA in body composition analyses [33]. Protocol guidelines provided by the manufacturer were used to record body mass via BIA [33,34]. The device used foot-to-foot measures, and the officer stood barefoot on the footplates.…”
Section: Height Body Mass and Body Fat Percentage (Bf%)mentioning
confidence: 99%